The Impact of E-Recruitment Implementation on Company Credibility, Candidate Selection Efficiency, and Process Transparency: Job Applicants’ Perspective - Adawiah, Andi; Putra, Aditya Halim Perdana Kusuma (International Review of Management and Marketing, 2024)
This study primarily focuses on the impact of e-recruitment implementation on company credibility, candidate selection efficiency, process transparency, and job applicants’ perspectives. Each of these aspects plays a crucial role in influencing how companies build their image, manage candidate selection processes, and how applicants respond to and interact with online recruitment processes. This study employs a mixed-method approach, collecting quantitative data from questionnaires and qualitative insights from interviews with respondents. The findings of this study give rise to conceptual ideas for future quantitative research through our discoveries. Our results emphatically state that the implementation of e-recruitment has significantly impacted on a company’s credibility, the efficiency of candidate selection, and process transparency from the perspective of job applicants. The use of innovative technology in e-recruitment enables companies to attract and recruit top talent more effectively while enhancing the applicant experience and optimizing the selection process. Associated with this study can be linked to the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). The adoption of innovative technology in e-recruitment can be accepted and adopted by job applicants if they perceive the technology as easy to use and beneficial in achieving their goals, such as obtaining desired employment.